Development of nursing students' performance in advanced cardiopulmonary resuscitation through role-playing learning model - Mohammad Nasr-Esfahani; Ahmadreza Yazdannik; Shahla Mohamadiriz (Wolters Kluwer Medknow Publications, 2019)
BACKGROUND: Role play is an educational method that is widely used for skill training because it forces students to think about people who play their role. Therefore, the present study was conducted with the aim of determining the effect of role-playing method education compared to traditional method education on the performance of nursing students in advanced cardiopulmonary resuscitation. MATERIALS AND METHODS: This is a semi-experimental study in which 70 nursing students in Isfahan University of Medical Sciences were randomly divided into two groups (35 students in each group): role-playing method and traditional method. The performance of nursing students in advanced cardiopulmonary resuscitation was evaluated using a performance checklist before and after training, in both groups. Data were analyzed by SPSS 14 software using descriptive and analytical tests of independent t-test and paired t-test. RESULTS: The paired t-test showed a significant difference between the mean performance scores after intervention between case and control groups, respectively (P = 0.01). Furthermore, independent t-test showed that there was a significant difference between the mean score of clinical performance in the two educational groups (P = 0.01). CONCLUSION: The results of the research show the effectiveness of role-playing method, which leads to improved performance of the students in advanced cardiopulmonary resuscitation. Therefore, this method can help the teachers to plan for the modification of educational programs in the course of apprenticeship and internship and improve the management skills of students' advanced cardiopulmonary resuscitation.